X+5(x-1)+1-x(x+1)=x+10-x(x+5)

Simple and best practice solution for X+5(x-1)+1-x(x+1)=x+10-x(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+5(x-1)+1-x(x+1)=x+10-x(x+5) equation:


Simplifying
X + 5(x + -1) + 1 + -1x(x + 1) = x + 10 + -1x(x + 5)

Reorder the terms:
X + 5(-1 + x) + 1 + -1x(x + 1) = x + 10 + -1x(x + 5)
X + (-1 * 5 + x * 5) + 1 + -1x(x + 1) = x + 10 + -1x(x + 5)
X + (-5 + 5x) + 1 + -1x(x + 1) = x + 10 + -1x(x + 5)

Reorder the terms:
X + -5 + 5x + 1 + -1x(1 + x) = x + 10 + -1x(x + 5)
X + -5 + 5x + 1 + (1 * -1x + x * -1x) = x + 10 + -1x(x + 5)
X + -5 + 5x + 1 + (-1x + -1x2) = x + 10 + -1x(x + 5)

Reorder the terms:
-5 + 1 + X + 5x + -1x + -1x2 = x + 10 + -1x(x + 5)

Combine like terms: -5 + 1 = -4
-4 + X + 5x + -1x + -1x2 = x + 10 + -1x(x + 5)

Combine like terms: 5x + -1x = 4x
-4 + X + 4x + -1x2 = x + 10 + -1x(x + 5)

Reorder the terms:
-4 + X + 4x + -1x2 = x + 10 + -1x(5 + x)
-4 + X + 4x + -1x2 = x + 10 + (5 * -1x + x * -1x)
-4 + X + 4x + -1x2 = x + 10 + (-5x + -1x2)

Reorder the terms:
-4 + X + 4x + -1x2 = 10 + x + -5x + -1x2

Combine like terms: x + -5x = -4x
-4 + X + 4x + -1x2 = 10 + -4x + -1x2

Add 'x2' to each side of the equation.
-4 + X + 4x + -1x2 + x2 = 10 + -4x + -1x2 + x2

Combine like terms: -1x2 + x2 = 0
-4 + X + 4x + 0 = 10 + -4x + -1x2 + x2
-4 + X + 4x = 10 + -4x + -1x2 + x2

Combine like terms: -1x2 + x2 = 0
-4 + X + 4x = 10 + -4x + 0
-4 + X + 4x = 10 + -4x

Solving
-4 + X + 4x = 10 + -4x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + X + 4 + 4x = 10 + 4 + -4x

Reorder the terms:
-4 + 4 + X + 4x = 10 + 4 + -4x

Combine like terms: -4 + 4 = 0
0 + X + 4x = 10 + 4 + -4x
X + 4x = 10 + 4 + -4x

Combine like terms: 10 + 4 = 14
X + 4x = 14 + -4x

Add '-4x' to each side of the equation.
X + 4x + -4x = 14 + -4x + -4x

Combine like terms: 4x + -4x = 0
X + 0 = 14 + -4x + -4x
X = 14 + -4x + -4x

Combine like terms: -4x + -4x = -8x
X = 14 + -8x

Simplifying
X = 14 + -8x

See similar equations:

| P-1=-5(p+2)+6p | | x=26.25-.25x | | a+24=3w^2+w-28 | | -(3x-3v-1)= | | 6x^3+6x^2-12x-12=0 | | .25(8z-4)=z+8-2 | | 5x+1=8x-20 | | 1/3*m=1/4*m | | 1/3*m=1/48m | | 77=11-0+e | | (x^4+y^4)dx+(3xy^3)dy=0 | | 4(x-2)+5=6-(x+5) | | X+5(x-1)+1-(x^1)=x+10-(x^5) | | 9x+12+6y+3y-10=180 | | 23x+17y=11 | | 9x+12+13y-10=180 | | 8k-3+8k=4K-3 | | X-1=3x-8+5x | | 2x-40=2y | | (4x^4y^9/z^8)^2 | | d^3-12d^2+36d=0 | | 5(30)+12=0 | | B+5=-9+7x | | 3/4-3/4x=1/8 | | -4+5v=-19 | | log(x)=-2.8831916 | | (1/2x)-7/4=-8/3 | | x^2+14x=23 | | 6(x-2)-3x=15 | | 21=6+3u | | 49z=1 | | -6x+9=7 |

Equations solver categories